2020
DOI: 10.1016/j.sjbs.2020.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of silver nanoparticles by Nigella sativa extract alleviates diabetic neuropathy through anti-inflammatory and antioxidant effects

Abstract: Green synthesis of silver nanoparticles has gained great interest among scientists. In view of this data, we conducted this study to identify the ameliorative effect of green synthesis of silver nanoparticles using Nigella sativa extract in diabetic neuropathy induced experimentally. In this study, 50 adult male albino rats were used and they were randomly divided into five groups; the first group was the healthy control group, the second group were the diabetic neuropathy diabetic neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(53 citation statements)
references
References 60 publications
(57 reference statements)
2
47
0
Order By: Relevance
“…In this approach, the aqueous fruit extract of the plant fulfilled reducing and stabilizing functions for the preparation, and the obtained AgNPs exhibited good catalytic and antibacterial activities [ 83 ]. Alkhalaf et al conducted a study to identify the effect of the green synthesis of AgNPs from a Nigella sativa plant extract, resulting in NPs that exhibit antioxidant activity [ 84 ].…”
Section: Green Synthesis Methods Of Aunps and Agnps From Plant Extmentioning
confidence: 99%
“…In this approach, the aqueous fruit extract of the plant fulfilled reducing and stabilizing functions for the preparation, and the obtained AgNPs exhibited good catalytic and antibacterial activities [ 83 ]. Alkhalaf et al conducted a study to identify the effect of the green synthesis of AgNPs from a Nigella sativa plant extract, resulting in NPs that exhibit antioxidant activity [ 84 ].…”
Section: Green Synthesis Methods Of Aunps and Agnps From Plant Extmentioning
confidence: 99%
“…In vitro, silver nanoparticles are also attributed with an anti-inflammatory effect by playing a role in the wound healing process due to TNF-α, interferons, and interleukin 1 as well as inhibition of COX-2 and MMP-3 expressions, and also have the potential to reduce the activity of TNF-α, which is involved in inflammatory processes [ 241 , 242 , 243 , 244 , 245 ]. AgNPs from the Piper nigrum extract were shown as selective cytokine inhibitory agents for IL-1β and IL-6 [ 246 ].…”
Section: Biomedical Application Of Agnpsmentioning
confidence: 99%
“…Although significant progress has been made in managing synthetic drugs for cardiovascular diseases, the search for indigenous cardioprotective agents is continuing. It has been shown that at least 30 food spices and herbs possess antioxidant properties such as Boswellia serrata , Nigella sativa, saffron and their major components such as thymoquinone, and safranol, [ [18] , [19] , [20] , [21] ]. Curcumin, the major yellow bioactive component of turmeric ( Curcuma longa L., Zingiberaceae), is a more recent discovery [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%